Etiological Profile of Referred Otalgias in a Tertiary Care Hospital - Karmacharya, Sameer; Sah, Santosh Kumar (Janaki Medical College Journal of Medical Science, 2020)
Background and Objectives Otalgia (earache) is one of the commonest presenting complaints of the patients visiting ENT OPD and wide varieties of otological diseases are associated with it. Surrounding structural pathology of head and neck can at times manifest as otalgia (because of complex innervations of ear) known as referred otalgia. The term Referred Otalgia applied when the ear examination is normal, so it is important to search for the secondary cause in other structures like pharynx, larynx, teeth, TM, nose, sinuses, salivary glands, neck, and rarely thoracic structures like esophagus, bronchus and heart. Material and Methods: A prospective study was conducted in the department of ENT – HNS in Janaki Medial College Teaching Hospital from Janaury 01, 2019 to July 31, 2020 with ear pain only. All patients are subjected to full history and ENT examination, in addition to examination of Temporo-mandibular joint (TMJ) and neck. Some patients were sent for audiological and radiological assessment according to the finding in the examination and some had maxillofacial or orthopedic consultation. Data were analyzed, primary and referred otalgia was recorded. Results: Out of 607 patients with otalgia, 243(40%) had referred otalgia of this 39% were men and 61% were women. Commonest etiology of referred otalgia was dental causes followed by TMJ dysfunction. 3% patient had underlying malignancies. 37% had right earache, 42% had left earache and 21% had bilateral earache. Conclusion: A thorough clinical examination of surrounding structures particularly teeth and TMJ should be done as significant number of patient suffered from referred otalgia and while doing this malignancy should be kept in mind as etiology.